Feasibility and Toxicity Profile of Hypofractionated Post- Mastectomy Radiation Therapy in Breast Cancer Patients - Velarasan, Kanmani; Ramasundaram, Deivanayagam; Prasad, Gopi (Asian Pacific Journal of Cancer Care, 2024)
Introduction: Post-mastectomy radiation therapy (PMRT) is a crucial part of breast cancer treatment. Hypofractionated radiation therapy, although more commonly used after breast conservation surgery, has emerged as a newer modality. However, there is a limited understanding of its feasibility and toxicity profile specifically in PMRT. This study aimed to describe the clinical outcomes and toxicity profile of breast cancer patients undergoing hypofractionated 3D conformal radiation therapy for PMRT. Materials and Methods: This retrospective study included breast cancer patients aged 18 and above who were eligible for adjuvant PMRT between April 2021 and October 2022. The treatment regimen consisted of 40.05Gy delivered in 15 fractions over 3 weeks using 3D conformal radiation therapy. Dosimetric parameters for target volumes and organs at risk were analyzed, and toxicities such as hematologic, dermatitis, and pharyngitis were monitored. Results: A total of 71 patients were included in the study, with 70 females and 1 male. The majority of patients (46%) belonged to the 46-55 years age group, with an age range of 34 to 85 years and a mean age of 52 years. Clinical Stage IIIA was the most common stage (29.5%), followed by Stage IIB (25.3%). The majority of patients received adjuvant chemotherapy (52%). The mean treatment time was 21 days, and all patients completed treatment without any major complications. The follow-up period ranged from 17 to 27 months. One patient expired due to a non- cancer-related cause, and four patients experienced disease progression or distant metastasis. Dosimetric analysis revealed satisfactory coverage of the planned target volume, with heart V17Gy ranging from 1.27% to 12.5% and heart V35Gy ranging from 0.16% to 7.2%. The most common adverse effect observed was dermatitis, followed by fatigue, throat pain, and shoulder pain. Blood parameters remained stable throughout the treatment course. Conclusion: Hypofractionated PMRT was well tolerated in the study group, with no major acute reactions or treatment interruptions observed. Our findings support the feasibility and safety of this treatment approach in breast cancer patients. Special attention should be given to respiratory motion management, particularly in left-sided disease, to achieve optimal dose constraints.